ANALISA KESADARAN PENGGUNA UNTUK MENINGKATKAN FITUR CUSTOMER KNOWLEDGE MANAGEMENT SYSTEM - Adi Chandra Setiawan (APMMI - Asosiasi Profesi Multimedia Indonesia, 2019)
Abstract - Custommer knowledge management (CKM) is the business model of the integration of interrelated concepts, techniques, and methodologies that are rooted in the people, process and technology and aims to create a profitable and loyal customers. On www.sikumis.com that is already running, but the feature has not been used optimally CKM. With the problem the authors look for indicators that affect the consciousness of the user in using the features of CKM. The methods used to SECI Model, Model Gebbert and KM Infrastructure, analysis method with likert Scale, Factor Analysis for data collection questionnaire. Of the 65 respondents fill out questionnaires in the test is valid and reliable. The results of the analysis of the factors resulting in the 3 factors. Dominant factor related to the use of information, communication, interaction, distribution and sharing of cultural knowledge, search and support structure orgrnisasi in the dissemination of knowledge. Keywords: Knowledge Management, Customer Knowledge Management, E-commerce, Analysis.